Identification of Medicinal Plants Used by the Community of Watumite Village, Nangapanda District, Ende Regency as a Biology Learning Media - Feliks A. Bara; Sardina Ndukang; Getrudis Wilhelmina Nau (BIODIK, 2023)
The aim of the research is to find out the types of medicinal plants used by the Watumite Village community, find out how to use each type of medicinal plant used and find out what medicinal plant booklets are used by the Watumite Village community. Watumite Village community is suitable for use as a biology learning medium. The type of research used is research and development with the ADDIE model (analysis, design, development, implementation, evaluation). This research uses a qualitative and quantitative descriptive approach. The qualitative approach used is to describe the types of medicinal plants used by the Watumite Village community. Meanwhile, a quantitative approach was carried out by calculating the results of the validation of the booklet developed which was then analyzed descriptively. The results of research on medicinal plant identification based on interviews with 10 respondents living in 4 hamlets in Watumite Village obtained 32 types of medicinal plants originating from 22 families. The findings of 32 types of medicinal plants packaged as Biology learning media in booklet form have been validated by material experts and media experts with a percentage value of 85% from material experts and 84% from media experts, declared valid. The conclusions from this research are: (1) There are 32 types of medicinal plants used by the community in Watumite Village; (2) The use of each type of medicinal plant includes the part of the plant used as medicine, the type of disease treated, and the method of processing; (3) Development of a Medicinal Plants booklet for the Watumite Village Community is categorized as suitable as a biology learning medium.